Performing at the Boundaries: Narratives of Early Career Engineering Practice. Issue 2 (4th May 2021) - Jesiek, Brent K.; Buswell, Natascha T.; Nittala, Swetha
Abstract : The realities of engineering practice remain opaque and constantly evolving, often leaving graduates underprepared for the workplace and employers dissatisfied with new employees. In this study we shed new empirical light on the lived working experiences of early career engineers in large manufacturing firms. We adopt boundary spanning as the primary framework for our research given growing recognition of its importance in the workplace and potential utility for conceptualizing engineering practice. We specifically address the research question: What kinds of boundary spanning do early career engineers experience in their daily work? Our study is based on interviews with 23 early career engineers analyzed using a thematic analysis approach to code for boundary spanning and other related themes. We then wrote third-person constructed narratives to holistically portray the day-to-day work of three participants. Our findings illustrate how engineers frequently encounter many different types of boundaries and perform specific boundary spanning activities. The narratives also illuminate early career progression, including evidence of increasing leadership responsibilities as engineers navigate evolving job role demands and organizational expectations. We conclude with directions for future research, and discuss how our findings speak to ongoing efforts to reimagine professional practice while improving engineering education and professional development.